EXPLORING THE IMPACTS OF AI USAGE IN ENGLISH LANGUAGE LEARNING - Nur Asiah Syafikah Mohamad Sazali; Nor Alifah Rosaidi; Nor Azira Mohd Radzi; Raisa Rastom; Surina Nayan, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This conceptual paper explores the advancing contribution of Artificial Intelligence (AI) in English language learning (ELL), highlighting its fundamental impacts and challenges. Changes in learners’ engagement towards English can be seen clearly with the integration of various AI learning programs in the educational setting. This paper discusses the impacts of AI towards language learning, including personalised learning experiences tailored to individual needs, 24/7 accessibility for learners and the provision of instant feedback on language skills. These features that belong to AI learning programs are helpful in enhancing learners’ engagement and motivation while learning English. However, the paper also emphasises the challenges presented by AI in language learning, such as the tendency to limit human interaction, overdependence on technology, and concerns about users’ data privacy. Moreover, AI systems may indirectly intensify cultural biases, limiting the inclusivity of learning tools. Ethical considerations are the key to the future of AI in educational settings. In conclusion, while AI has the potential to reshape language learning, it is essential to balance technology with traditional learning methods and address the related challenges. The paper also proposes for future research to explore the long-term effects of AI on language acquisition and learner motivation.